UiTM medic get together - Ab Azis, Norasikin (Faculty of Medicine, 2021)
Living during this COVID-19 pandemic has caused a significant impact on the physical and psychological well being of many throughout the world. Students in higher education have their own sets of worries that they are dealing with now. Most are concerned about their health, lack of social interaction, self-isolation, and difficulty focusing on their studies online.